مدى فاعلية التحسين المستمر للخدمات المصرفية في تحقيق الميزة التنافسية ) دراسة ميدانية في المصارف الاسلامية في سورية( - المارديني, مزنة; موصلي, سليمان (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى دراسة تأثير التحسين المستمر للخدمات المصرفية بعناصره الثلاث: البحوث والتطوير، التكنولوجيا الحديثة، الابداع والابتكار في تحقيق الميزة التنافسيةفي المصارف الاسلامية في سورية. وقد تم اختيار هذا الموضوع نظراً للأهمية التي يحتلها التحسين المستمر للخدمات المصرفية في المصارف الاسلامية لكل من العملاء والمصرف، إذ أن التحسين المستمر للخدمات المصرفية يؤدي إلى رضا العملاء ،الذي يمكن المصرف الاسلامي من تحقيق الميزة التنافسية. وتمثلت عينة الدراسة من العاملين في المصارف الاسلامية في محافظة دمشق، كون المصارف الاسلامية تعد من المصارف الرائدة في سورية وتقدم كافة الخدمات التي تقدمها المصارف الخاصة. وقد تم جمع البيانات عن طريق استمارة الاستبيان التي تكونت من محورين ، الأول يتعلق بقياس المستويات المتحققة من التحسين المستمر للخدمات المصرفية في المصارف الاسلامية في سورية ، والثاني يتعلق بقياس المستويات المتحققة من الميزة التنافسية في المصارف الاسلامية في سورية. واستخدمت وسائل إحصائية كالوسط الحسابي والانحراف المعياري ومعامل الارتباط بالاضافة إلى نماذج الانحدار البسيط والمتعدد وذلك للتعرف على اتجاهات أفراد العينة واختبار الفرضيات . وقد أوضحت النتائج أن العاملين في المصارف الاسلامية في سورية يعتقدون أنها استطاعت تحقيق مستويات جيدة من التحسين المستمر للخدمات المصرفية لديها ،وأن التحسين المستمر للخدمات المصرفية يكون من خلال تشجيع البحث والتطوير واستخدام التكنولوجيا الحديثة و دعم الابداع والابتكار، وهذا بدوره يحقق الميزة التنافسية، مع التأكيد على أفضلية استخدام التكنولوجيا الحديثة. كما صيغت مجموعة من التوصيات كان من أهمها الاستمرار في تحسين وسائل تقديم الخدمة المصرفية وسرعة أدائها، وذلك باستخدام التكنولوجيا المتطورة والمجهزة ذات التقنية العالية، فضلاً عن التأكيد على تمييز خدماتها وابتكار خدمات جديدة وتطبيق إستراتيجية التميز. This research aims to examine the impact of three dimentions of continuous improvement (i.e., Research and Development, New Technologies, and Innovation) of banking services in the Islamic banks in Syria, on the realization of competitiveness. This topic has been selected due to the importance of Continuous Improvement of Banking Services in Islamic banks for both the customer and the bank, taking into consideration that this guarantees customer satisfaction, thus achieving the desired goal of competitiveness. The study samples covers a number of workers in Islamic banks in Damascus Governorate, given the fact that Islamic banks being pioneers in Syria in that they offer all the services provided by private banks. The data, collected by means of a questionnaire, comprises two parts; one for measuring the levels achieved in the Continuous Improvement of Banking Services of Islamic banks in Syria, and the other for measuring the levels achieved in terms of competitiveness of Islamic banks in Syria. Statistical methods of Mean analysis, Standard Deviation, correlation coefficient, simple and multiple regression models to identify the trends of the sample and test the hypotheses in question. The findings indicate that Islamic banks in Syria have been able to achieve very good levels of Continuous Improvement of Banking Services. Results suggest that the above mentioned three dimentions significantly affect the competetivemness with priority given to adapting new technologies. A set of recommendations are suggested, the most important of which is the urgent need for more attention be given to the Continuous Improvement of banking services, through using high technologies in addition to differentiate and introduce new services and the application of differentiation strategy.